The influence of service dog partnerships on perceived and objective sleep quality for military veterans with PTSD - Bristol, Stephanie; Leighton, Sarah C.; Schwichtenberg, A. J.; Campbell, Rebecca L.; Ashbeck, Erin L.; Taylor, Daniel J.; Bedrick, Edward J.; O'Haire, Marguerite E. (Frontiers in Sleep, 2024)
Introduction Sleep disturbances, fear of sleep, and nightmares are among the most reported symptoms for military service members and veterans (henceforth “veterans”) with posttraumatic stress disorder (PTSD), potentially contributing to treatment resistance and heightened suicidality. Despite available evidence-based interventions, many veterans still report difficulties. The complementary intervention of a psychiatric service dog may contribute to improvements in sleep quality for veterans with PTSD. Methods This preregistered, non-randomized clinical trial evaluated the association between service dog partnership and sleep at 3 month follow-up. Participants were N = 155 veterans with PTSD (81 in the service dog group and 74 waitlisted controls). Measures included self-report surveys measuring PTSD severity (PTSD Checklist for DSM-5, PCL-5) sleep quality (Pittsburgh Sleep Quality Index, PSQI), sleep disturbance (PROMIS Sleep Disturbance), and fear of sleep (Fear of Sleep Inventory-Short Form, FoSI-SF); morning sleep diaries measuring nightmares; and wrist-worn actigraphy. Regression models and mediation analyses were performed. Results Service dog partnership was significantly associated with better subjective sleep [PSQI: mean difference −2.2, 95% CI (−3.4, −1.1), p < 0.001; PROMIS Sleep Disturbance: −3.6, 95% CI (−6.3, −0.9), p = 0.004; FoSI-SF: −6.6, 95% CI (−9.7, −3.5), p < 0.001] and odds of nightmares [OR = 0.45, 95% CI (0.26, 0.76), p = 0.003]. Service dog partnership was not associated with a change in actigraphy-based measures of sleep [sleep onset: −4.5, 95% CI (−12.2, 3.2); sleep duration: −4.7, 95% CI (−25.9, 16.6); wake after sleep onset: 6.0, 95% CI (−2.1,14.1); sleep efficiency: −0.4, 95% CI (−3.4, 2.5)]. The estimated proportion of the effect of service dogs on PTSD severity mediated by fear of sleep was 0.26 [95% CI (0.10, 0.48)]. Discussion Compared to the control group, veterans with service dogs for PTSD reported better sleep quality, less sleep disturbance, and less fear of sleep after 3 months. However, service dog partnership was not associated with differences in actigraphy-measured sleep. These findings demonstrate the impact of psychiatric service dog partnerships on sleep quality for veterans with PTSD.